2012
DOI: 10.1007/s00417-012-2000-1
|View full text |Cite
|
Sign up to set email alerts
|

Tempol protects against intravitreous indocyanine green-induced retinal damage in rats

Abstract: Tempol significantly attenuates ICG-induced toxicity in rat retinas and may therefore be considered for further evaluation as accompanying treatment in ICG-assisted chromovitrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In contrast, a previous study with ICG 0.5% in the same model showed a much more pronounced b-wave reduction that remained significant even 14 days after ICG application. 17 This accords with the results of other ERG studies 3 in which b-wave reduction was significant even after 2 months of dye exposure, and the retinal structure was altered. Other studies found significant b-wave reductions for ICG 0.5%; these persisted for o4 weeks but were accompanied by anatomical changes.…”
Section: In Vivo Testing Of a New Cyanine Dye S Thaler Et Alsupporting
confidence: 90%
See 3 more Smart Citations
“…In contrast, a previous study with ICG 0.5% in the same model showed a much more pronounced b-wave reduction that remained significant even 14 days after ICG application. 17 This accords with the results of other ERG studies 3 in which b-wave reduction was significant even after 2 months of dye exposure, and the retinal structure was altered. Other studies found significant b-wave reductions for ICG 0.5%; these persisted for o4 weeks but were accompanied by anatomical changes.…”
Section: In Vivo Testing Of a New Cyanine Dye S Thaler Et Alsupporting
confidence: 90%
“…Electrodes were placed as described previously. 17 Ten minutes before starting ERG measurements, the pupils were fully dilated with tropicamide and the dim red light was turned off.…”
Section: Electroretinographymentioning
confidence: 99%
See 2 more Smart Citations
“…The present study reinforces the toxic profile of ICG showing a reduction of RPE cell viability in all tested concentrations and time exposure. More recently some papers have been dedicated to reduce the ICG-related toxicity with free radical scarvengers (tampol), less concentration, short time exposure, or iodine-free solution such as IfCG [35] [36, 37]. …”
Section: Discussionmentioning
confidence: 99%